Preliminary validation of Global Leadership Initiative on Malnutrition criteria in cancer patients: A cross-sectional study - Huang, Zhe-Yu; Zhang, Rui; Yin, Rui-Kang; Wang, Shi-Jie; Han, Jiang-Long; Wang, Qi-Lan; Fu, Zhen-Ming (Journal of nutritional oncology, 2023)
Abstract Background The Global Leadership Initiative on Malnutrition (GLIM) has been used in China since 2019. This study aimed to test the use of the GLIM criteria in Chinese cancer patients and to compare the diagnostic performance of the GLIM criteria with the Patient-Generated Subjective Global Assessment (PG-SGA) and modified PG-SGA (mPG-SGA). Methods A total of 2,000 cancer patients were consecutively screened using the Nutritional Risk Screening 2002 instrument on admission. Patients at nutritional risk (Nutritional Risk Screening 2002 score ≥ 3) were enrolled to obtain the complete GLIM, PG-SGA, and mPG-SGA criteria. To evaluate the convergent validity, Spearman correlation analysis was used to compare the test-retest reliability of the GLIM criteria and its results with the scores of various nutritional tools and objective parameters. Kruskal-Wallis tests and χ2 tests were used to test the discriminant validity among groups with different nutritional status. We calculated the sensitivity, specificity, positive predictive value, and negative predictive value for the various tools. Results There were 562 patients found to be at nutritional risk, accounting for 28.1% of all patients. One hundred seventy-four patients (8.7%) were diagnosed as moderately malnourished, and 333 patients (16.6%) were severely malnourished based on the PG-SGA. When assessed using the GLIM criteria, 185 patients (9.3%) were diagnosed as moderately malnourished and 311 patients (15.5%) were severely malnourished. The content validity of the GLIM criteria was 95%, evaluated by 60 medical staff members. The test-retest reliability was good. For the diagnosis of malnutrition versus the PG-SGA, the sensitivity of the GLIM was "good" (90.5%; 95% confidence interval [95% CI] = 88.0%-93.1%), with a positive predictive value of 92.5% (95% CI = 90.2%-94.9%), but the specificity and negative predictive value were "poor." Similar results were obtained when the mPG-SGA was used as the criterion. Conclusions Overall, this cross-sectional study suggests that the GLIM criteria comprise a valid and reliable tool to assess the nutritional status of Chinese cancer patients.